AGO recommendations for the surgical therapy of the axilla after neoadjuvant chemotherapy: 2021 update = AGO-Empfehlungen zur operativen Therapie der Axilla nach neoadjuvanter Chemotherapie : Update 2021 - Friedrich, Michael; Kühn, Thorsten; Janni, Wolfgang; Müller, Volkmar; Banys-Paluchowski, Maggie; Kolberg-Liedtke, Cornelia; Jackisch, Christian; Krug, David; Albert, Ute-Susann; Bauerfeind, Ingo; Blohmer, Jens; Budach, Wilfried; et al. (Geburtshilfe und Frauenheilkunde, 2021)
For many decades, the standard procedure to treat breast cancer included complete dissection of the axillary lymph nodes. The aim was to determine histological node status, which was then used as the basis for adjuvant therapy, and to ensure locoregional tumour control. In addition to the debate on how to optimise the therapeutic strategies of systemic treatment and radiotherapy, the current discussion focuses on improving surgical procedures to treat breast cancer. As neoadjuvant chemotherapy is becoming increasingly important, the surgical procedures used to treat breast cancer, whether they are breast surgery or axillary dissection, are changing. Based on the currently available data, carrying out SLNE prior to neoadjuvant chemotherapy is not recommended. In contrast, surgical axillary management after neoadjuvant chemotherapy is considered the procedure of choice for axillary staging and can range from SLNE to TAD and ALND. To reduce the rate of false negatives during surgical staging of the axilla in pN+CNB stage before NACT and ycN0 after NACT, targeted axillary dissection (TAD), the removal of > 2 SLNs (SLNE, no untargeted axillary sampling), immunohistochemistry to detect isolated tumour cells and micro-metastases, and marking positive lymph nodes before NACT should be the standard approach. This most recent update on surgical axillary management describes the significance of isolated tumour cells and micro-metastasis after neoadjuvant chemotherapy and the clinical consequences of low volume residual disease diagnosed using SLNE and TAD and provides an overview of this yearʼs AGO recommendations for surgical management of the axilla during primary surgery and in relation to neoadjuvant chemotherapy.
Gesehen am 29.01.2022